The effect of the appearance of our self-representation in a virtual world on our behavior: a survey - Christofi, Maria; Michael-Grigoriou, Despina (My University, 2016)
Our self-representation in a virtual world can influence our behavior and actions there. This survey studies the existing literature in these aspects, and concludes on the impact of your virtual appearance on your behavior. The process applied involves the analyses of key points relevant to body ownership, virtual reality, embodiment, and human behavior.
Keywords: Embodiment; Body ownership; Human behavior